TANTANGAN HUKUM DAN HAK ASASI MANUSIA DALAM MITIGASI PERUBAHAN IKLIM BERKEADILAN DI D. I. YOGYAKARTA - Baskoro, Aji (WICARANA, 2025)
The Special Region of Yogyakarta, known as a hub of culture and education, faces pressing challenges in addressing climate change driven by intensive economic activities and natural resource exploitation. The impacts of climate change are intrinsically linked to environmental concerns and social justice, disproportionately affecting vulnerable groups such as farmers, urban poor communities and riverbank residents. Adopting a legal and human rights-based framework is crucial to ensuring inclusive and equitable protection for all. This study examines the legal and human rights challenges in mitigating climate change and evaluates the relevance of John Rawls’ theory. Employing a normative juridical method with statute and conceptual approaches, the research combines regulatory analysis with the principles of substantive justice. The findings highlight weak enforcement of environmental laws as a major legal barrier, alongside inadequate protections for vulnerable groups and limited community participation, which hinder progress in achieving human rights objectives. The study underscores the need for enhanced inter-agency coordination, integration of human rights perspectives, and active multi-stakeholder engagement. Prioritizing the protection of vulnerable groups is emphasized as a fundamental aspect of substantive justice. Key recommendations include strengthening legal enforcement, fostering community involvement in policy-making, and advancing research on technological innovation and community-driven solutions.